2016
DOI: 10.3354/meps11928
|View full text |Cite
|
Sign up to set email alerts
|

Induced defence to grazing by vertebrate herbivores: uncommon or under-investigated?

Abstract: There are many examples of macroalgae inducing defence in response to small invertebrate herbivores like amphipods, isopods, and gastropods but few cases of induction in response to vertebrate macrograzers like herbivorous fishes. This may be because larger grazers rapidly consume large quantities of seaweed before induction can occur, thus selecting for constitutive rather than induced defences. Alternatively, the pattern could occur because induction due to feeding by macrograzers is less commonly investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Metabolic variations may arise from different nutrient concentrations and herbivory pressure between sites. Nevertheless, Canard islet and Larégnère are marine protected areas so herbivory pressure must be higher compared to other sites, potentially leading to an increase in algal chemical defense as suggested in other works 6 . To further investigate this hypothesis, it would be interesting to test the bioactivity of MeOH fractions among sites.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Metabolic variations may arise from different nutrient concentrations and herbivory pressure between sites. Nevertheless, Canard islet and Larégnère are marine protected areas so herbivory pressure must be higher compared to other sites, potentially leading to an increase in algal chemical defense as suggested in other works 6 . To further investigate this hypothesis, it would be interesting to test the bioactivity of MeOH fractions among sites.…”
Section: Discussionmentioning
confidence: 86%
“…They are involved in chemical communication and play diverse ecological functions in macroalgae. Even if the best known and studied ecological role of these metabolites is the deterrence against competitors and herbivores 5,6 , they can also act as defense against pathogens 7,8 ( e . g .…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of scientific research indicated that ocean warming has caused ecological impacts on various marine flora and fauna species across the globe, with a range of species marching away from their native homes in search of cooler climes [ 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ]. With heatwaves sweeping through oceans twice as much as they did in the early 1990s, many biodiversity hotspots around the world are on the verge of imminent collapse.…”
Section: At a Glance: Key Defence Strategies Of Marine Macroalgae Aga...mentioning
confidence: 99%
“…Tropical macroalgal taxa have been reported to produce a higher diversity of metabolites compared to their temperate counterparts, dominated by halogenated metabolites, terpenoids, acetogenins, and phenolics [ 127 , 128 ]. Mainly regulated by developmental, genetic, and environmental factors, these metabolites play diverse ecological functions in macroalgae, from being deterrent against herbivores to defenders to fight against specific pathogens and competitors for space with other marine organisms [ 127 , 129 , 130 ].…”
Section: At a Glance: Key Defence Strategies Of Marine Macroalgae Aga...mentioning
confidence: 99%